Safety of dipeptidyl peptidase 4 inhibitors: a perspective review. (June 2014) - Karagiannis, Thomas; Boura, Panagiota; Tsapas, Apostolos
Dipeptidyl peptidase 4 (DPP-4) inhibitors are a relatively new class of oral antihyperglycemic agent that enhance insulin secretion by reducing degradation of endogenous glucagon-like peptide 1. Currently, sitagliptin, vildagliptin, saxagliptin, linagliptin and alogliptin have been approved by the US Food and Drug Administration or the European Medicines Agency for use in patients with type 2 diabetes. Their glycemic efficacy has been well documented; however, data regarding their long-term safety are as yet inconclusive. While preclinical studies have indicated a potential cardioprotective effect of DPP-4 inhibitors, current clinical data from cardiovascular safety trials suggest a neutral effect on cardiovascular outcomes. Moreover, postmarketing experience has given rise to concerns about specific adverse events, including pancreatitis and hypersensitivity reactions. This review summarizes available evidence regarding safety of DPP-4 inhibitors. Overall, DPP-4 inhibitors appear to be a safe option for patients with type 2 diabetes. However, close pharmacovigilance is necessary to address the uncertainty regarding pancreas-related adverse events, while their potential impact on cardiovascular outcomes will be further elucidated after completion of more long-term studies.